SALIENCE AND ACCEPTABILITY IN SPANISH MANNER VERBS: A PRELIMINARY VIEW - Feist, Michele I.; Rojo, Ana; Cifuentes Ferez, Paula (International Journal of English Studies, 2009)
It has been long noted that Spanish does not license the use of manner verbs when describing telic motion events, particularly when they involve boundary crossing (Aske, 1989; Slobin & Hoiting, 1994). The only exception to this constraint seems to be punctual acts, especially vertical boundary crossing situations, such as tirarse a la piscina (lit. ‘throw oneself into the pool’) (Naigles et al., 1998). Slobin (2004, 2006) has pointed out the low salience of manner in Spanish; the Spanish manner verb lexicon is not as extensive and frequently used as that of high manner salient languages like English, and as a result Spanish speakers are thought to attend less to manner than English speakers. In this study, we ask whether Spanish speakers would accept a manner verb in a boundary-crossing event, when manner of motion is made highly salient, either by contextual or by cultural means. Our research, though still preliminary, suggests both contextual manner salience and cultural manner salience increase the acceptability of Spanish manner verbs in boundary-crossing situations.